DVB‐S2X‐enabled precoding for high throughput satellite systems. (18th June 2015) - Arapoglou, Pantelis‐Daniel; Ginesi, Alberto; Cioni, Stefano; Erl, Stefan; Clazzer, Federico; Andrenacci, Stefano; Vanelli‐Coralli, Alessandro
Summary: Multi‐user multiple‐input multiple‐output (MU‐MIMO) has allowed recent releases of terrestrial long‐term evolution (LTE) standards to achieve significant improvements in terms of offered system capacity. The publication of the DVB‐S2X standard and particularly of its novel superframe structure is a key enabler for applying similar interference management techniques –such as precoding– to multibeam high throughput satellite (HTS) systems. This paper presents results from the European Space Agency‐funded R&D activities concerning the practical issues that arise when precoding is applied over an aggressive frequency re‐use HTS network. In addressing these issues, the paper also proposes pragmatic solutions that have been developed in order to overcome these limitations. Through the application of a comprehensive system simulator, it is demonstrated that important capacity gains (beyond 40%) are to be expected from applying precoding even after introducing a number of significant practical impairments. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The publications of the DVB‐S2X standard and particularly of its novel superframe structure are a key enabler for applying interference management techniques ‐ such as precoding ‐ to multibeam high throughput satellite (HTS) systems. This paper presents results from European Space Agency funded R&D activities concerning the practical issues that arise when precoding is applied over an aggressive frequency re‐use HTS network. It is demonstrated that important capacity gains (beyond 40%) are to be expected from applying precoding.